Do estimates of women’s control over income and decisionmaking vary across nationally representative survey programs? - Raghunathan, Kalyani; Mahmoud, Mai; Heckert, Jessica; Ramani, Gayathri V.; Seymour, Greg (Springer, 2025)
Empowering women is an explicit aim of Sustainable Development Goal (SDG) 5 and underpins 12 of the 17 SDGs. It is also a key objective of other pan-national agreements, such as the Comprehensive African Agriculture Development Programme. Tracking global progress toward these goals requires being able to measure empowerment in ways that are consistent and comparable—both within and across countries. However, empowerment is a complex concept, hard to quantify, and even harder to standardize across contexts. Two large survey programs—Feed the Future and the Demographic Health Surveys—ask women about two aspects of empowerment, their control over income and input into decisionmaking. Each program uses a different set of questions administered to different sub-populations of women. We use data from 12 countries to show that large within-country inter-survey differences persist even after efforts to harmonize questions and samples. Where available, we compare the FTF and DHS with the Living Standards and Measurement Surveys-Integrated Surveys on Agriculture. We present several hypotheses related to survey structure and survey administration to explain these inter-survey differences. We then either test for or rule out the role of these competing theories in driving differences in levels and in associations with commonly used characteristics. Standardizing survey measures of decision making and control over income and how they are administered is important to track progress toward the SDGs; meanwhile, caution should be exercised in comparing seemingly similar survey items across survey programs.